2016
DOI: 10.3389/fmicb.2016.00874
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cefquinome PK/PD Parameters and Emergence of Resistance of Staphylococcus aureus in Rabbit Tissue-Cage Infection Model

Abstract: In order to explore the relationship between different antibiotic dosing regimens and selective enrichment of resistant strains, tissue-cage infection model was established in rabbits to study relationship between cefquinome pharmacokinetic/pharmacodynamic parameters and the change of susceptibility of Staphylococcus aureus (S. aureus). In this model, above 108 CFU/mL of S. aureus culture were exposed to cefquinome concentrations below the MIC99 (the minimal concentration that inhibits colony formation by 99% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
5
29
1
Order By: Relevance
“…Our results differ from many in vitro studies and a few in vivo studies in which the evolution of resistance was reduced at higher doses [71][72][73]. The discordance between these studies and ours likely arises from the existence of the so-called inverted U, where resistance evolution is minimized at very low or very high doses and maximized somewhere in-between [3,4].…”
Section: Dose and The Emergence Of Resistancecontrasting
confidence: 99%
“…Our results differ from many in vitro studies and a few in vivo studies in which the evolution of resistance was reduced at higher doses [71][72][73]. The discordance between these studies and ours likely arises from the existence of the so-called inverted U, where resistance evolution is minimized at very low or very high doses and maximized somewhere in-between [3,4].…”
Section: Dose and The Emergence Of Resistancecontrasting
confidence: 99%
“…In the veterinary field, the tissue-cage model is widely used for PK/PD studies and has been reported useful in several species, such as calves (Bengtsson and Greko, 2002), piglets (Zhang et al, 2014), goats (Sidhu et al, 2010), and rabbits (Xiong et al, 2016). However, there are few reported studies of macrolide drugs on PK/PD models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, resistance is thought to be promoted when antimicrobial concentrations fall within the MSW (11). This has been shown using in vitro studies and studies in animals (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%